An incentive-based evolutionary algorithm for participatory sensing - Teerawat Kumrai (2018)
© 2014 IEEE. Participatory sensing enables to broadly collect information from mobile devices with embedded sensors. However, users have to use limited energy on the mobile devices as well as have to pay more communication fee when reporting sensory data to service providers. It is important to give them incentives to send information in participatory sensing systems. In this paper, we propose a novel incentive mechanism for participatory sensing based on the evolutionary algorithm. Our proposed algorithm is evaluated by extensive simulations and its performance is compared with state-of-the-art algorithms. The simulation results demonstrate that our algorithm successfully increases the number of participating users while it can also uniformly expand the coverage of a sensing area.